(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: Description of post-operative nutritional knowledge of colorectal cancer patients at Viet Tiep Friendship Hospital in 2025 Research methods: Cross-sectional descriptive study at the Oncology Center and the Department of Oncology Surgery - Palliative Care, An Dong facility, Viet Tiep Friendship Hospital in 2025. Results: Cancer patients need a diverse diet to ensure adequate and balanced nutrition, which is essential for supporting the body’s vital functions and maintaining good health during treatment. However, only 66.7% of patients agree with this viewpoint, while the remaining 33.3% believe that it is not necessary to eat a variety of foods. Most patients demonstrate a good understanding of the need to supplement their nutrition (76.2%) and to avoid fatty foods (77.1%). Additionally, a significant majority recognizes the importance of drinking enough water (97.1%) to aid in recovery. However, knowledge about eating a variety of foods is still relatively low at 66.7%, and only 51.4% understand the need to avoid red meat. Furthermore, understanding of vitamin and mineral supplements is limited, with only 40% knowledgeable about them. Similarly, many patients (61.9%) disagree with the benefits of whole grains, and a substantial 56.2% do not consider omega-3 essential to their diet. Conclusion: Patients’ nutritional knowledge was limited, particularly regarding the role of whole grains (38.1%), omega-3 or EPA (43.8%), and micronutrients (40%). In contrast, awareness about the importance of drinking enough water (97.1%) and the need to limit fatty foods (77.1%) was significantly higher. These gaps in knowledge underscore the necessity for comprehensive nutrition education programs to improve patient awareness.